Adoption of musharakah financing model for long term development of small medium sized enterprises (SMES) - Abd. Rahman, Nur Hasnida; Mohamed, Mustafa Omar (2017)
One of the important issues that have been discussed in the study of Small and Medium Enterprise ("SMEs") is their difficulty in getting access to external financing, particularly from the banking institutions. This problem occurs because the banking institutionsare predominantly debt based financing system which requires SMEs to fulfill banking requirementsof providing adequate collateral and payment of high interest rates. SMEs inability to fulfill these requirements obliges them to rely heavily on internal financing and this limits their long-term growth and development. As financing is crucial to ensure SMEs' long-term growth and development, this study has been conducted to examine the potential of Musharakah as a viable alternative financing for SMEs. Accordingly, the Musharakah financing model was developed and a survey among SMEs firms in Malaysia was conducted to validate the potential of Musharakah financing model for SMEs. The results show that Musharakah financing has potential in providing SMEs' with a greater access to financing. Therefore, the model needs to be given a premier attention so that SMEs will have greater access to financing for their longterm growth and expansion.